Screening of new improved water yam (Dioscorea alata) genotypes for the preparation of amala in Nigeria - Ukpabi, U.J.; Omodamiro, R.M.; Ikeorgu, J.G.; Asiedu, Robert (International Institute of Tropical Agriculture, 2010)
Production of improved water yam (Dioscorea alata) genotypes that are suitable for the preparation of amala (a popular darkish Nigerian food) would likely enhance the economic importance of the crop in Nigeria. Fermented flour (oven dried and sun dried) made from tubers of eight new improved D.alata genotypes (TDa 00/00364, TDa 00/00194, TDa 00/00103, TDa 00/00104, 99/00240, 99/01176, 98/01166, Um 680) and two landraces (TDa 92-2, Ominelu) were reconstituted into amala, and organoleptically evaluated. Relevant characteristics of the experimental yam tubers, and their intermediate products (chips and flour), were also evaluated for desirable qualities. Results showed that the tubers shape could affect the percentage peel loss of the tubers during processing. The dry matter content of the experimental fresh tubers varied from 20.05% to 45.63%, while the moisture content of the oven dried fermented yam flour (elubo) samples (used for the amala preparation) ranged from 8.30% to 9.80%. The colour observed in the amala samples varied from light brown to black. Though most of the experimental genotypes could be used in preparing amala, only TDa 00/00194 and TDa 00/0364 were highly rated (in relevant sensory parameters) for the preparation of the foodstuff (which is traditionally made from processed tubers of some Diosocrea rotundata cultivars).